2022
DOI: 10.1016/j.jmig.2021.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Same Day Discharge after Laparoscopic Surgery in Gynecologic Oncology

Abstract: To identify factors associated with same day discharge (SDD) after laparoscopic surgery in gynecologic oncology. Design: Retrospective cohort. Setting: Teaching hospital. Patients: Total of 800 patients having minimally invasive surgery in the division of gynecologic oncology during a 20month period. Intervention: Minimally invasive surgery cases were reviewed for determinants of SDD to identify factors that could improve the SDD rate. Measurements and Main Results: During the study period, 800 minimally invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Overall, there were no significant differences in patient age, BMI, tobacco use, or alcohol use between groups. Further patient characteristics for this study population have been previously reported [14,17]. There were no differences between the type of minimally invasive approach between the two groups or the need for mini-laparotomy (5.2% vs 4.3%, p = 0.78).…”
Section: Resultsmentioning
confidence: 88%
“…Overall, there were no significant differences in patient age, BMI, tobacco use, or alcohol use between groups. Further patient characteristics for this study population have been previously reported [14,17]. There were no differences between the type of minimally invasive approach between the two groups or the need for mini-laparotomy (5.2% vs 4.3%, p = 0.78).…”
Section: Resultsmentioning
confidence: 88%
“…They predicted SDD rates to improve only to 48.5% by 2029 unless focused SDD improvement measures were instituted [6]. In our review of the literature, we found that an ERAS MIS protocol in gynecologic oncology improved the rates of SDD from a baseline of approximately 30% to 50-70%, depending on the extent of measures in place (patient education, standardized orders, prioritizing surgery earlier in the day, early Foley removal, reduction of opioids, and prophylactic anti-emetics) [9,15,17]. There remain barriers to SDD, and surgeon preference has been shown to be a major contributor, which is why it is imperative to develop robust eligibility criteria, based on safety data to determine those who are most able likely to benefit [4,9].…”
Section: Discussionmentioning
confidence: 88%
“…Subsequently, a number of studies have reported similar outcomes to enhance SDD rates with ERAS implementation in MIS gynecologic oncology surgery patients. Brancazio et al, in a pre/post-ERAS MIS implementation study of 800 patients, 351 of whom were in the post-intervention arm, found that the standardized ERAS protocol alone increased the rates of SDD from 39.3% to 48.9% [9]. The safety and feasibility of SDD in ERAS MIS gynecologic oncology surgery was investigated in a retrospective cohort study by Wield et al, where 1124 patients were evaluated.…”
Section: Decrease Length Of Stay and Increased Rates Of Same-day Disc...mentioning
confidence: 99%
“…Forty percent of hysterectomies are now completed via a minimally invasive approach, which has increased significantly over the past 20 years ( ACOG Committee, 2018 , Bixel et al, 2022 ). Most women who undergo surgery for endometrial cancer undergo a minimally invasive hysterectomy (MIH), and the oncologic outcomes of this approach are comparable to laparotomy ( Bishop et al, 2018 , Brancazio et al, 2021 , Hospital, 2022 ). Additionally, compared to open surgery, MIH is associated with numerous benefits, including lower rates of peri -operative complications, faster recovery time, and decreased length of hospital stay ( Di Donato et al, 2021 , Farhat et al, 2012 , Fountain and Havrilesky, 2017 , Gallotta et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%